2005
DOI: 10.1111/j.1471-4159.2005.03245.x
|View full text |Cite
|
Sign up to set email alerts
|

Age‐associated changes in mRNA levels of Phox2, norepinephrine transporter and dopamine β‐hydroxylase in the locus coeruleus and adrenal glands of rats

Abstract: Age-related changes in the gene expression of the transcription factors, Phox2a and 2b, and two marker proteins, norepinephrine transporter (NET) and dopamine b-hydroxylase (DBH), of noradrenergic neurons were characterized in the locus coeruleus (LC) and adrenal glands using in situ hybridization. Analysis of changes was performed in rats that were 1-23 months of age. Compared to 1-month-old rats, there was a 62% increase of Phox2a messenger RNA (mRNA) in the LC of 3-month-old rats, and a decline of 37% in 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 65 publications
1
21
0
Order By: Relevance
“…Our results suggest that NET might contribute to the decrease in myocardial β 1 -AR mRNA with aging. The NET change appears accordant with previous observations (Shores et al, 1999;Zhu et al, 2005), which showed that NET mRNA expression in locus coeruleus (LC) was significantly decreased with aging in rats, and the level of NET in the LC of 23-month-old rats showed less than half of that found in the 1-month-old rats (Zhu et al, 2005). These previous findings also indicate that there was an age-dependent decrease in myocardial NET binding sites by 36% in elderly patients [(60±3) years] without apparent heart failure, and NET activity was ~50% lower than that in children [(14±3) years] (Leineweber et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…Our results suggest that NET might contribute to the decrease in myocardial β 1 -AR mRNA with aging. The NET change appears accordant with previous observations (Shores et al, 1999;Zhu et al, 2005), which showed that NET mRNA expression in locus coeruleus (LC) was significantly decreased with aging in rats, and the level of NET in the LC of 23-month-old rats showed less than half of that found in the 1-month-old rats (Zhu et al, 2005). These previous findings also indicate that there was an age-dependent decrease in myocardial NET binding sites by 36% in elderly patients [(60±3) years] without apparent heart failure, and NET activity was ~50% lower than that in children [(14±3) years] (Leineweber et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…These studies indicate that Phox2a/2b may participate in direct transcriptional activation of DBH and NET genes in vitro . Our study showed that a significant reduction in mRNAs of Phox2 in the LC and adrenal glands of aging rats was accompanied by a decline in mRNA levels of NET and DBH (Zhu et al. 2005), suggesting a possible relationship between Phox2 genes and these marker genes in noradrenergic neurons after birth.…”
mentioning
confidence: 60%
“…(2) They are essential and determinant for the generation and development of noradrenergic neurons during embryogenesis; (3) Phox2a genes are commonly considered to be persistently present in adult brains; and (4) Phox2a/2b can directly transactivate the promoters of DBH and NET, both characteristic factors of noradrenergic neurons. Our previous study demonstrated that reduced Phox2 mRNA levels in the LC of aged rats was accompanied by parallel reduction of DBH and NET mRNA levels (Zhu et al, 2005), indicating the possibility of a causal relationship between Phox2 genes and expression of the noradrenergic phenotypes during aging. If so, then delivery of related transcription factors into the LC of brains to up-regulate the phenotype may be a strategy to arrest or counteract the neurodegenerative process in aging or degenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether these genes still have modulatory effects on noradrenergic neurons and phenotypes in adult brains has not been elucidated. Our previous in vivo study showed that a significant reduction in mRNAs of NET and DBH in the LC and adrenal glands of aging rats was paralleled with a decline in mRNA levels of Phox2 (Zhu et al, 2005), suggesting a possible relationship between these marker genes and Phox2 genes in noradrenergic neurons after birth. Furthermore, in vitro investigations (Yang et al, 1998, Stanke et al, 1999, Kim et al, 2002, Fan et al, 2009) demonstrated direct transcriptional activation of DBH and NET genes by Phox2 genes.…”
mentioning
confidence: 94%